PENERAPAN MODEL PEMBELAJARAN BERBASIS MASALAH UNTUK MENINGKATKAN KEMAMPUAN BERWUDHU DENGAN MENGGUNAKAN METODE PRAKTEK SISWA PADA MATA PELAJARAN FIQIH KELAS 1 MI AL-MUSLIM - Nahnu Zaidatunisa (Al Hikmah: Jurnal Studi Keislaman, 2025)
Abstract, To be able to learn something well, we need to hear, see, ask questions about it, and discuss it with others. Not only that, students need to "do it", namely describing something in their own way, showing examples, trying to practice skills and doing tasks that require the knowledge they have gained. This study used three rounds of action research. Each round consists of four stages, namely: design, activities and observations, reflection, and revision. The target of this study was grade I students. The data obtained were in the form of formative test results, observation sheets for teaching and learning activities. From the results of the analysis, it was found that student learning achievement increased from cycle I to cycle III, namely, cycle I (73.34%), cycle II (80.00%), cycle III (93.34%) The conclusion of this study is that problem-based contextual learning can have a positive effect on the Ability to Perform Ablution with the practice method of grade I Students, and this learning model can be used as an alternative to fiqh learning. Keywords: fiqh lessons, contextual, problem-based